2020
DOI: 10.1177/0197918319882634
|View full text |Cite
|
Sign up to set email alerts
|

When Does Social Capital Matter for Migration? A Study of Networks, Brokers, and Migrants in Nepal

Abstract: The study of social capital has been one of the strongest areas of recent advance in migration research, but there are still many questions about how it works and why it has varying effects in studies of different places. In this article, we address the contextual variation in social capital’s effects on migration by considering migration brokers. We argue that destinations for which migration is logistically difficult to arrange give rise to brokerage industries and hypothesize that brokers, in turn, substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…There exists an ample consensus in the existing literature about the main causes for both flows immigrants and refugees [14]. Thus, the list of thirty items correspond to the categories of factors that include economic variables, globalization, political variables, social variables, cultural variables and access variables [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Other items were obtained from the items included in the studies of secondary houses as these are also related to the objective of the study [31][32][33][34][35].…”
Section: Questionnaire and Datamentioning
confidence: 99%
“…There exists an ample consensus in the existing literature about the main causes for both flows immigrants and refugees [14]. Thus, the list of thirty items correspond to the categories of factors that include economic variables, globalization, political variables, social variables, cultural variables and access variables [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Other items were obtained from the items included in the studies of secondary houses as these are also related to the objective of the study [31][32][33][34][35].…”
Section: Questionnaire and Datamentioning
confidence: 99%
“…Yet, individuals with low capital endowments would be exposed to higher levels of security risk. Bourdieu defined four different forms of capital endowments: economic, social, cultural, and symbolic capital (Bourdieu, 1986 ; Ozbilgin and Tatli, 2005 ; Williams et al, 2020 ). Economic capital is the endowment of financial and material resources that individuals accumulate.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing health challenges is also an important part of this social adaptation process. However, subsequent studies have suggested that the adaptation process of immigrants is not linear, but full of selection and segregation, caused by incompatibilities between individual characteristics and social environment [ 29 , 30 , 31 ]. Since formal support is absent or unstable, individuals’ social behaviors are more dependent on informal social support, represented by social networks, which then have a greater impact on their health.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their economic value, the receiving units then pay more attention and support to them, and they also find it easier to obtain the welcome of residents in Chinese society. Therefore, individuals’ needs for ethnic affiliation decrease, and this also reduces the ethnic norms that restrict their interactions [ 30 ]. Relatively speaking, immigrants from more developed countries are less dependent on the Motherland-Net, thus limiting the expansion of their Motherland-Net.…”
Section: Introductionmentioning
confidence: 99%